Palm Art to therapeutic Properties: Henna-A Potential Medicinal Plant - Shafqat Zaidi; Abbas Zaidi; Syaifuddin Amir; Rana Mohsin Ali; Amira Alifia Syabani (International Journal of Technology and Education Research, 2023)
Henna (Lawsonia inermis, Litheracae) has been used cosmetically and medicinally from ancient times. Henna is a medicinal plant that has been widely used as an antioxidant, and antimicrobial. Sometimes it is applied directly to the affected area for itching, eczema, scabies, wounds, and burning of the skin. Currently, several scientific investigations are aimed at the isolation and identification of active constituents of Henna. This article indicates the most salient pharmacological actions of Henna. The main pharmacological actions of henna and compounds isolated therefrom include anti-microbial, anti-inflammatory, anti-apoptotic, anti-hyperglycemic, and anti-lipidemic. Henna is considered a safe herbal medicine with only a few insignificant adverse/ side effects. So this article aims at reviewing the most salient recent reports on these investigations. The main pharmacological actions of henna and compounds isolated therefrom include lawsone, coumarine, anti-microbial, anti-tumorigenic, anti-inflammatory, anti-apoptotic, anti-hyperglycemic, and anti-lipidemic.